2007
DOI: 10.1002/ajmg.a.32097
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense‐mediated decay and the molecular pathogenesis of mutations in SALL1 and GLI3

Abstract: Mutations in SALL1 and GLI3 are responsible for human limb malformation syndromes. The molecular pathophysiology of these mutations is incompletely understood, and many conclusions have been drawn from studies performed in the mouse. We identified truncating mutations in SALL1 and GLI3 in patients with limb malformation and studied the contribution of nonsense-mediated decay (NMD) to the expression of mutant mRNA in patient-derived fibroblasts. Quantification of the relative proportions of mutant and wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
2
42
0
1
Order By: Relevance
“…Because the mutant mRNA is detectable and appears similarly abundant to the wild-type mRNA, we conclude that the mutant transcript escapes NMD. This has been confirmed for human SALL1 in a recent publication [Furniss et al, 2007].…”
Section: Mutant Mousetranscripts Escape Nonsense-mediated Decaysupporting
confidence: 73%
See 1 more Smart Citation
“…Because the mutant mRNA is detectable and appears similarly abundant to the wild-type mRNA, we conclude that the mutant transcript escapes NMD. This has been confirmed for human SALL1 in a recent publication [Furniss et al, 2007].…”
Section: Mutant Mousetranscripts Escape Nonsense-mediated Decaysupporting
confidence: 73%
“…These SOX10 mutations were predicted to produce either dominant truncated proteins or haploinsufficiency based on their ability to be degraded by NMD, whereas SALL1 mutations unexpectedly escape NMD destruction. This work and a recent work by Furniss et al [2007] establish SALL1 as one of several examples that do not follow the expected NMD path [Asselta et al, 2001;Danckwardt et al, 2002;Romao et al, 2000] and suggest that determining the mechanism of NMD escape may suggest in utero treatment strategies to lessen TBS abnormalities. Because NMD efficiency varies between individuals and is tissuespecific [Bateman et al, 2003;Kerr et al, 2001], the function of this pathway may also contribute to phenotypic variability in syndromes such as TBS.…”
Section: Discussionmentioning
confidence: 83%
“…Previous known exceptions to these correlations were described, for example, the recurrent c.2374C4T associated with a typical GCPS phenotype. 9,11,19,20 These exceptions may be explained by a variable contribution of nonsense-mediated decay 12 or by the formation of unstable proteins with a very short half-life, effective nulls. Only 10 GCPS probands of our series did fulfill all criteria suggested by Biesecker et al 6 namely preaxial PD, cutaneous syndactyly, widely spaced eyes and macrocephaly.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Truncating mutations in the middle third of the gene generally cause PHS, resulting in a constitutive repressor protein. By contrast, haploinsufficiency resulting from chromosomal rearrangements, but also missense, splicing or truncating mutations elsewhere in the gene cause GCPS by loss of the DNA-binding capacity 11 or activation of nonsense-mediated mRNA decay, 12 or by the formation of an unstable or mislocalized protein. 13,14 In this study, we report on the clinical and molecular data of a French cohort of 76 individuals from 55 families carrying a GLI3 molecular defect.…”
Section: Introductionmentioning
confidence: 99%
“…10 Kiefer et al (2003) demonstrated that truncated Sall1 mediates interaction with all Sall family members and could interfere with the normal function of all Sall proteins. 10 Furniss et al (2007) reported a heterozygous 995delC mutation in exon 2 of SALL1 escaped nonsense-mediated decay and produced a truncated protein acting in a dominant-negative manner. 11 Nonsense-mediated decay efficiency varies between individuals and is tissue specific, which may contribute to phenotypic variation in the patients carrying the same mutations.…”
Section: Discussionmentioning
confidence: 99%